2016
DOI: 10.1016/j.ijscr.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of GIST tumors located near the gastroesophageal junction: Case report and review of the literature

Abstract: HighlightsThere are several endoscopic, laparoscopic and open surgical procedures available for the management of GIST tumors near the GE junction.We present a case-report utilizing both endoscopy and laparoscopy to facilitate resection using the non-touch lesion-lifting technique.Pathology demonstrated a 4.7 cm GIST. The patient was discharged on post-operative day 3 with no complications.We include a full literature review and describe the various combined modalities available for successful resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Therefore total laparoscopic proximal gastrectomy has been proposed by some authors [ 4 , 5 , 7 ]. Still, this is considered too invasive for the resection of GISTs [ 8 , 9 ]. To solve this issue, Tagaya et al, in 2002 reported the technique of intragastric resection; balloon-type ports were inserted into the gastric lumen via the gastric wall to remove the tumor, yet this equipment wasn't always available and created a difficulty for the surgical team [ [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore total laparoscopic proximal gastrectomy has been proposed by some authors [ 4 , 5 , 7 ]. Still, this is considered too invasive for the resection of GISTs [ 8 , 9 ]. To solve this issue, Tagaya et al, in 2002 reported the technique of intragastric resection; balloon-type ports were inserted into the gastric lumen via the gastric wall to remove the tumor, yet this equipment wasn't always available and created a difficulty for the surgical team [ [10] , [11] , [12] ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are still debates about the laparoscopic resection of large GISTs exceeding 5 cm, there are some new studies that confirm the safety and feasibility of this method [ 4 , 5 , 9 , 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of LR are less bleeding, less pain, faster return of bowel function, earlier initiation of oral regimen, shorter hospital stay, faster recovery, smaller incisions and better view of identifying the progression of the tumor to the liver or peritoneum [ 2 , 5 , 9 , 14 , 17 ]. In IHC CD117 (C-kit) is positive in 95–100% of GISTs, and CD34 is positive in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If they are uniformly benign, the long-term outcome is excellent [ 29 ]. Furthermore, the standard treatment for GISTs is open or laparoscopic surgical resection with free margins [ 30 ], although recent studies demonstrated the feasibility and safety of endoscopic resection through an endoscopic submucosal dissection (ESD) technique for small tumors. GISTs have been associated with a relatively low recurrence rate during long-term follow-up despite little R 0 resection rate [ 31 ].…”
Section: Discussionmentioning
confidence: 99%